Hubungan Kondisi Lingkungan Rumah, Sosial Ekonomi, dan Perilaku Masyarakat Dengan Kejadian Filariasis di Kecamatan Pekalongan Selatan Kota Pekalongan - Windiastuti, Ike Ani; Suhartono, Suhartono; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2013)
Filariasis is a disease caused by filarial worms and transmitted by mosquito as vector. Indonesia is an endemic for filariasis with Mf-rate of 3.1%, while Mf-rate in Pekalongan was 3.58 % in year 2010. In the year of 2012 there were no data Mf-rate but there was an increasing of filariasis cases, with the highest level in South Pekalongan district with 84 cases. Based on the preliminary surveys and information from District Health Office (DHO) Pekalongan, there were some factors for the transmission of it, including environmental and behavior factors. This research aimed to determine the condition of the house’s environment, socioeconomic and behavior associated with the incidence of filariasis in Pekalongan. It was an observational research using a case control design. The subjects was 80 cases and 80 controls. Data was collected through laboraory examination, observation and interviews. Data were analyzed using univariate, bivariate with chi-square and continued with multivariate logistic regression. The results of surgery mosquitoes found positive for mosquito larvae of filaria. Statistical analysis found 4 (four) variables had associated significantly with the incidence of filariasis in Pekalongan, including breeding places of mosquitos (pvalue:0,006, OR:2,672 95 % CI:1,376-5,189), the resting places of mosquitos (pvalue:0,025, OR:2,170 95 % CI:1,146-4,107), out of the house habit (pvalue:0,010, OR:2,453 95 % CI:1,282-4,693) and the use of insect repellents (pvalue:0,006, OR:2,636 95 % CI:1,365-5,090). This study concluded that the environmental factors and poor people behaviors influenced the incidence of filariasis, while the presence of wire netting, the type of works and income level did not affect the incidence of filariasis in Pekalongan. Key word : lymphatic filariasis, environmental factors, community behavior, Pekalongan city.